Mellan styrning och pedagogisering. En analys av hur förskolans ledningspersoner förstår förskolans jämställdhetsuppdrag - Tobias K. Axelsson; Sara Frödén (Utbildning & Demokrati, 2021)
Between governance and pedagogisation: An analysis of preschool managers’ understanding of their gender equality duty in the Swedish preschool. This article explores how local preschool managers – that is principals, heads of childcare and education departments, and chairs of childcare and education political committees – understand their gender equality mission. It is based on three focus groups with thirteen participants in three Swedish municipalities. Theoretically, the article conceptualises gender equality as simultaneously an ‘empty signifier’ and organisational process. The analysis shows that preschool managers understand gender equality on three levels: state/politically; municipal/organisationally; and practically/pedagogically. Based on the results of the empirical analyses, we suggest that further gender equality work in preschools needs to: find a balance between politicisation and administration; be organised horizontally and allow for knowledge transformation; and be actively led by preschool principals in order to not make pre-school teachers responsible for implementing the gender equality duty.